DESIGN AND RESEARCH ON MODULAR CUTTERHEAD AND MAIN DRIVE OF VARIABLE MEASUREMENT RECTANGLE PIPE JACKING MACHINE - ZHANG HaoWen; LUO HongMei; ZHENG Jun; GUO Tao; WANG YuChen (Jixie qiangdu)
In order to achieve the rapid measurement change of the rectangular pipe jacking machine and expand the application scope of the equipment, based on the DPLEX drive form, a modular cutterhead and main drive of the variable measurement rectangular pipe jacking machine are designed. One set of cutterhead is equipped with two sets of drives to form a set of module that is easy to disassemble and replace. Multiple modules must be used in combination to ensure that at least 4 crankshafts support a set of cutterhead. Based on the force analysis of the module, the ANSYS was used to carry out static analysis and modal analysis on the cutterhead and crankshaft, and the stress value, deformation and inherent frequency of the cutterhead and crankshaft under the maximum load condition were obtained; Through the rigid-flexible coupling dynamics simulation, the crankshaft load spectrum is obtained. And the fatigue analysis of the crankshaft is carried out based on nCode DesignLife. The results show that: in the construction of soft soil layer, the maximum stress of the cutterhead is 229.7 MPa, which is lower than the yield strength of the material, the safety factor is 1.55, the inherent frequency of the cutterhead at the first six orders range from 179.3 Hz to 196.5 Hz; the maximum stress of the crankshaft is 491.4 MPa, which is located at the front spindle at the neck fillet, the safety factor is 1.89, and the inherent frequency of the crankshaft at the first six orders range from 333.4 Hz to 1 304.5 Hz. The main fatigue damage points of the crankshaft are concentrated at the fillet of the front main journal, the minimum number of cycles is 3.37×10~7, and the theoretical life is 165 928 h. It can meet the tunneling needs of the pipe jacking machine.